2014
DOI: 10.1007/s00595-014-0903-7
|View full text |Cite
|
Sign up to set email alerts
|

External sphincter resection for lower rectal and anal canal adenocarcinoma: achieving anal preservation with oncological and functional satisfaction

Abstract: Intersphincteric resection (ISR) has recently been performed for very low rectal cancer, whereas abdominoperineal resection (APR) is typically reserved for cancers extremely close to the anal verge and/or when the depth of tumor invasion is suspected to involve the intersphincteric space. This is because impairment of anal function is considered unavoidable if the external sphincter (ES) is excised. We describe our technique of ISR with ES resection and discuss its outcomes. This surgical technique may offer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…To address these issues, we have developed CSR based on total ISR. This approach expands the resection scale beyond visceral structures on the tumour-affected side (similar to the approach in partial external sphincter resection for tumours invading the ISS to ensure a negative CRM [17]), distal to the Hilton white line (by removing a partial subcutaneous portion of the EAS and perianal skin) to ensure a safe after diverting stoma closure are comparable to those reported in the literature for partial intersphincteric resection or low anterior resection, suggesting that the CSR procedure yields better functional outcomes compared to conventional t-ISR, which is typically associated with a higher rate of postoperative bowel dysfunction [6][7][8]. Employing the CSR technique modifies the concept of decision-making for sphincter-preserving surgery, which is finally independent of the distance between the tumour's lower edge and the anal verge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, we have developed CSR based on total ISR. This approach expands the resection scale beyond visceral structures on the tumour-affected side (similar to the approach in partial external sphincter resection for tumours invading the ISS to ensure a negative CRM [17]), distal to the Hilton white line (by removing a partial subcutaneous portion of the EAS and perianal skin) to ensure a safe after diverting stoma closure are comparable to those reported in the literature for partial intersphincteric resection or low anterior resection, suggesting that the CSR procedure yields better functional outcomes compared to conventional t-ISR, which is typically associated with a higher rate of postoperative bowel dysfunction [6][7][8]. Employing the CSR technique modifies the concept of decision-making for sphincter-preserving surgery, which is finally independent of the distance between the tumour's lower edge and the anal verge.…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, we have developed CSR based on total ISR. This approach expands the resection scale beyond visceral structures on the tumour‐affected side (similar to the approach in partial external sphincter resection for tumours invading the ISS to ensure a negative CRM [17]), distal to the Hilton white line (by removing a partial subcutaneous portion of the EAS and perianal skin) to ensure a safe DRM (confirmed negative by intra‐operative frozen section), while preserving the dentate line mucosa and IAS on the tumour‐free side to the greatest extent possible. The key to this technique is to ensure oncological safety through extensive excision of the anal canal on the tumour‐affected side while achieving acceptable functionality through compensation by preserving the dentate line mucosa and IAS on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular insufficiency is the major complication of TPP with delayed CAA, in the present study shown in four patients, due to the compression of the anal canal on the exteriorized colonic stump. This adverse effect can be solved using the posterior incision of halfthickness anal sphincter 18 and concomitant scar debridement, without any clinically significant effect on anal contraction.…”
Section: Discussionmentioning
confidence: 99%
“… 36 With its acceptable oncologic outcome and preservation of anal function, adaptation of ISR with CAA has increased and has largely replaced APR; nevertheless, APR is still indicated when there is infiltration of the intersphincteric space to avoid leaving tumor cells at the resection margin. 37 …”
Section: Sphincter Preservationmentioning
confidence: 99%
“…Partial removal of the external sphincter is also performed if there is invasion into the intersphincteric space and/or external sphincter muscles. 37 38 A Japanese study group defined three types of ISRs: Total ISR is performed when the tumor has spread beyond the dentate line, and involves complete removal of the internal sphincter. Subtotal ISR is performed when the distal edge of the tumor is >2 cm from the dentate line, and involves resection of two-thirds of the internal sphincter.…”
Section: Sphincter Preservationmentioning
confidence: 99%